A Note on Value Distribution of the Product of a Meromorphic Function and Its Higher Order Derivatives - Banerjee, Dibyendu; Pal, Papai (Journal of Informatics and Mathematical Sciences, 2025)
In the present note, we consider the value distribution of the product of a meromorphic function and its higher order derivatives and generalise a result of Lahiri and Dewan (Value distribution of the product of a meromorphic function and its derivative, Kodai Mathematical Journal 26 (2003), 95 – 100).